PENGARUH KUALITAS DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN LAPTOP ACER TIPE ASPIRE 4752 DI KELURAHAN SEPANG JAYA KECAMATAN KEDATON BANDAR LAMPUNG - Anggara, Robi; Wibasuri, Anggalia (Jurnal Manajemen dan Keuangan, 2012)
The Acer Laptop got the market share decreasing significantly as 1,6%. This decreasing is a problem together with increasing of HP and Toshiba indentify the brands in Acer market share. The purpose of this research is to know how big the influence of quality and price simultaneously and partially toward the Aspire 4752 type Acer Laptop at Sepang Jaya societies ward of Kedaton District Bandar Lampung. The research hypothesis is predicted that there is an influence significantly between quality and price simultaneously and partially toward consumersâ purchasing decision. The research result showed regression correlation Y= 12,645 + 0,126 X1 + 0,151 X2 is obtained too R square value is 12,6 %. While the rest is 87,4 % is influenced by other factors out from observed factors. Based on the simultaneous test (F test) that is F count variable and price simultaneously have a significant influence toward purchasing decision. Based on partial (t test) is obtained t count of quality variable is 2,976 is bigger than t table is 1,661 and price variable is obtained t count 1,559 is less than t table is 1,661, so Ho is received and Ha is rejected, it means that price variable partially has a significant influence toward the Aspire 4752 type Acer Laptop at Sepang Jaya Ward societies of Kedaton District Bandar Lampung.Keywords : Quality, Price and Purchasing Decision